Physical and mechanical changes in thermal modified wood: A review - Atif Hodžić; Mohsen Bahmani (Zaštita Materijala)
In Europe, wood is a crucial construction material that has experienced a surge in use for building applications in recent years. To enhance its dimensional stability and durability, thermal modification is a widely accepted commercial technology. Thermal modification is a popular technique that alters the properties of wood, improving its resistance to decay and increasing its dimensional stability. The process involves heating wood to high temperatures under controlled conditions, leading to chemical reactions that result in various physical and mechanical changes. This paper will discuss the effects of thermal modification on the physical properties of wood, such as density, moisture content, and color, as well as its impact on the mechanical properties, including strength, stiffness, and hardness. Additionally, the review will examine the factors that influence the degree of modification, such as temperature, duration, and wood species. Finally, the paper will conclude with an overview of the current state of research in this field and identify potential avenues for future investigation.